Competências socioemocionais na formação do enfermeiro: representações de estudantes, docentes e enfermeiros assistenciais - Teixeira, Joaquim Ismael de Sousa (2022)
Given the demands of the current health scenario, the development of socio-emotional skills (CSE) consistent with what the academic and professional environment demands becomes urgent. It is believed, however, that health education is not yet completely structured to encourage students to have social and emotional skills that can improve their professional and human development. The present study aims to apprehend the representations made by professors, students and care nurses about the development and mobilization of socio-emotional skills in the training and work process of nurses. This is an exploratory-descriptive research, of a qualitative and quantitative nature, with data collection and analysis carried out from January to August 2022. The collection of information took place through interviews with 87 respondents; [i] 20 professors and 44 students of an undergraduate course in Nursing and, [ii] 23 nurses working in a referral hospital for the northern region of the state of Ceará. Data analysis was performed using the framework of Social Representations (JODELET, 2002; MOSCOVICI, 2003) supported by the technique of Collective Subject Discourse (CSD) by Lefevre and Lefevre (2014), with the aid of DSCsoft software for tabulation. and data processing. This research is part of a larger project entitled: Socio-emotional competences in Health Education: from diagnosis to the construction of an intervention program, approved by the Research Ethics Committee under number 5,255,261. In the analysis process, 28 discourses of the collective subject were identified, divided into seven categories originated from the interviews, 18 of them representing equally, 21.42% (n=6) of speech participation among professors, students and nurses. The other 10 CSD, present in category three, which had the highest number of speeches, 35.71% of the total, were constructed from speeches mixed with central ideas of the three audiences that addressed each of the five macro competences. Social- emotional competences were seen as necessary for the teaching-learning process and for the nurse's work environment, even though the initiatives seen at graduation are still scarce. Given the degree of importance of emotions that was attributed by the three audiences, the development of these skills is a prerogative for a comprehensive training that meets the needs of the current job market, in addition to being a protective factor for the physical and emotional health of professionals in the area.